A Study On Different Modalites Of Diagnosis And Treatment Of Right Iliac Fossa Mass (Indian Journal of Applied-Basic Medical Sciences, 2020)
Background: Patients with mass in the right iliac fossa may consent the surgeon,  paediatrician or gynaecologist. Thus, proper Knowledge of anatomy and pathological  process that occur within the abdomen are essential for a Clinical diagnosis and  management. The objective of this study was to interpret etiopathology, clinical  presentation, differential diagnosis and management of mass in the right iliac fossa.  Methodology: 50 cases with mass in the right iliac fossa (RIF) were included in the study.  Investigations such as Ultrasonography, colonoscopy and CT scan were done.  Results: During this study period, a total number of 10 cases of appendicular abscess and 22  cases of appendicular mass were taken. 11 cases of ileocecal Koch’s were encountered.  Patients had constitutional symptoms like pain, fever, weight loss etc. Specimens was  observed after Right hemicolectomy, interval appendicectomy, ileoascending resection  anastomosis microscopically and histopathological diagnosis. 2 cases of carcinoma  ascending colon and 2 cases of carcinoma caecum were seen. Filling defect and mucosal  irregularities was seen in Contrast enema.  Conclusions: This study conclude that appendicular mass is the commonest pathology in  right iliac fossa amongst all and conservative treatment followed by interval  appendicectomy is the best way of treatment. Ileocecal tuberculosis is second and  Carcinoma of the colon is third common causes for mass in the right iliac fossa. These cases  having a good prognosis, if properly treated and diagnosed. The other rare causes of mass in  the right iliac fossa are intussusception, psoas abscess.
Keywords: Carcinoma of the colon; Intussusception; Psoas abscess; Ileocecal tuberculosis